Alain L. Locke : biography of a philosopher - Harris, Leonard, 1948- (University of Chicago Press, 2008)
Often called the father of the Harlem Renaissance, Locke promoted, influenced, and sparred with such figures as Langston Hughes, Zora Neale Hurston, Jacob Lawrence, and many more. This biography narrates the story of his profound impact on 20th-century America's cultural and intellectual life.